Effect of pre-task music on sports or exercise performance - Smirmaul, Bruno P. [UNESP] (Edizioni Minerva Medica, 2017)
INTRODUCTION: Pre-task music is a very common strategy among sports competitors. However, as opposed to in-task music, the scientific evidence to support its ergogenic effects on either sports or exercise performance is limited. This brief review critically addresses the existing literature investigating the effects of pre-task music on sports and exercise performance, focusing on the methods and results of experimental studies, and offers basic and practical recommendations. EVIDENCE ACQUISITION: In July 2015, a comprehensive literature search was performed in Web of Science, PubMed, and Google Scholar using the following key words in combination: pre-task music, pre-test music, pre-exercise music, exercise performance, sports performance. The literature search was further expanded by both hand searching review articles on the topic and by searching the reference lists from the articles retrieved for any relevant references. Overall, a total of 15 studies in 14 articles were included. EVIDENCE SYNTHESIS: Pre-task music research has been unsystematic, methodologically limited and infrequent. Using this review as a starting point to overcome previous methodological limitations when designing future experiments may contribute to the development of pretask music research, which is still in its infancy. CONCLUSIONS: Currently, there is no sufficient evidence to support the overall ergogenic effects of pre-task music on sports or exercise performance. Nonetheless, pre-task music has showed a likely ergogenic effect on shorter and predominantly anaerobic tasks such as grip strength, Wingate test, and short-duration sports or sports-like tasks, in contrast to longer and predominantly aerobic tasks.
Keywords: Athletic performance; Central nervous system stimulants; Music